What is "Islamic" Art? Between Religion and Perception, by Wendy M. K. Shaw. (13th October 2021) - Korn, Lorenz
Abstract : What is "Islamic" Art? Between Religion and Perception, by Wendy M. K. Shaw. Cambridge University Press, 2019. 382pp., 34 b/w figures and 18 colour plates. Hb. € 36, 75. ISBN-13: 9781108474658.